Influence of the Three Gorges Reservoir Impoundment on Xiannvshan Fault Activity - Zhang Jiayu; Zhang Lili; Zhang Yaowen; Yao Yunsheng; Li Haoran; Dai Yiming; Wang Renlong; Hu Caixiong (Geofluids)
Since the initial impoundment and commissioning of the Three Gorges Reservoir in June 2003, seismic activity surrounding the reservoir region has undergone substantial changes. Leveraging geological and hydrogeological data from the Three Gorges Reservoir area, this study statistically analyzes the historical water level and earthquake catalog within the reservoir. By examining the correlation between reservoir water levels and earthquake frequency, the relationship between seismicity along the Xiannvshan fault and water level is analyzed. Additionally, the ArcGIS software is employed to evaluate the spatial pattern of earthquake epicenters during the filling of the Three Gorges Reservoir, with the goal of elucidating the impact of water impoundment at the Three Gorges on the activity along the Xiannvshan fault. The results demonstrate the following. (1) There is a complex process of “continuous loading, permeation and saturation, rebound and rebalancing” in the crust of the reservoir head area during the impoundment of the Three Gorges Reservoir area, and the activity of the Xiannvshan fault is closely related to the reservoir water level. (2) At the 135 m impoundment stage, Xiannvshan fault activity is mainly affected by reservoir water level and is positively correlated with reservoir water level. At the 156 m impoundment stage, reservoir water load is still the main influencing factor of Xiannvshan fault activity, but the permeability of reservoir water is enhanced in this stage. (3) The earthquake epicenters near the northern section of the Xiannvshan fault are clustered during the 175 m experimental impoundment stage. During the continuous loading stage, the reservoir water load is still the main control factor of the Xiannvshan fault, and the seismic activity is significantly enhanced. From November 2010 to November 2013, during the permeation and saturation stage, the dominant factor of Xiannvshan fault activity changed from reservoir water load to reservoir water infiltration along the Xiannvshan fault. The period from 2013.11 to 2014.5 was a vertical rebound stage, and the infiltration effect of reservoir water had a more significant impact on Xiannvshan fault activities.